2014
DOI: 10.1111/trf.12780
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic red blood cell exchange may be beneficial in the management of sickle cell disease in pregnancy

Abstract: This study has demonstrated that prophylactic RBCX during pregnancy is a feasible and safe procedure for prevention of complications. Given the decrease in the risks of transfusion, RBCX warrants further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(73 citation statements)
references
References 48 publications
3
64
1
Order By: Relevance
“…10,15 The proportion of patients receiving prophylactic transfusion and needing additional on-demand transfusions was not reported in the majority of studies and varied widely in the studies in which it was reported (5.6-60.7%). 14 In the single RCT conducted by Koshy et al, 16 the prophylactic transfusion group received simple or partial exchange transfusions to achieve the following targets: hemoglobin of 100 to 110 g/L, Hct of 33%, and HbS ,35%. Transfusions were initiated between 8 and 14 weeks of GA in three quarters and between 20 and 26 weeks in one quarter of participants.…”
Section: Summary Of Management and Transfusion Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…10,15 The proportion of patients receiving prophylactic transfusion and needing additional on-demand transfusions was not reported in the majority of studies and varied widely in the studies in which it was reported (5.6-60.7%). 14 In the single RCT conducted by Koshy et al, 16 the prophylactic transfusion group received simple or partial exchange transfusions to achieve the following targets: hemoglobin of 100 to 110 g/L, Hct of 33%, and HbS ,35%. Transfusions were initiated between 8 and 14 weeks of GA in three quarters and between 20 and 26 weeks in one quarter of participants.…”
Section: Summary Of Management and Transfusion Protocolsmentioning
confidence: 99%
“…13 Furthermore, reports assessing the effect of prophylactic RBC transfusions on pregnancy outcomes in SCD have been inconsistent. [14][15][16][17][18][19] Thus, the objective of this study was to systematically review the impact of prophylactic transfusion compared with on-demand transfusion (defined as transfusion instituted to treat complications) on maternal and neonatal adverse pregnancy outcomes in pregnant women with SCD.…”
Section: Introductionmentioning
confidence: 99%
“…The HbS gene is found in high frequency in many parts of Africa, India, the Middle East, the Mediterranean area, and aparts of Turkey 8 . The primary manifestations of SCD are chronic hemolytic anemia and episodes of severe pain crises due to vasoocclusion 9 . Repeated vasooclusive crisis can affect multiple organ systems, and individuals with SCD have increased risks of stroke, renal dysfunction, pulmonary hypertension, retinal disease, and avascular necrosis 9 .…”
Section: Discussionmentioning
confidence: 99%
“…The primary manifestations of SCD are chronic hemolytic anemia and episodes of severe pain crises due to vasoocclusion 9 . Repeated vasooclusive crisis can affect multiple organ systems, and individuals with SCD have increased risks of stroke, renal dysfunction, pulmonary hypertension, retinal disease, and avascular necrosis 9 . RBC transfusions remain a cornerstone treatment for acute and chronic complications in SCD 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation